Composite of few-layer MoO3 nanosheets with graphene as a high performance anode for sodium-ion batteries. Issue 24 (1st June 2016) - Sreedhara, M. B.; Santhosha, A. L.; Bhattacharyya, Aninda J.; Rao, C. N. R.
Abstract : A composite anode comprising of a 3D network of few-layer MoO3 nanosheets with an optimum amount of rGO exhibits excellent Na-ion cyclability over wide ranging values of operating current densities. Ultrathin nanosheets of MoO3 are synthesized by oxidation of MoS2 nanosheets and are tagged with optimum amounts of rGO. Abstract : Identification of an appropriate anode material is one of the major challenges for rechargeable Na-ion batteries. Layered MoO3 is a potential alternative as it can reversibly store large amounts of sodium. However, MoO3 is a poor electronic conductor and undergoes large volume changes during repeated cycling. Ultrathin nanosheets of 1–3 bilayers of MoO3 are synthesized starting from the oxidation of few-layer MoS2 nanosheets. The MoO3 nanosheets are subsequently chemically tagged with optimum amounts of rGO leading to the formation of a 3D MoO3 –rGO composite. The MoO3 –rGO composite exhibits remarkable electrochemical stability, cyclability and high rate capability over a wide range of operating currents (0.05–1 C). This simple and novel material design strategy of MoO3 –rGO provides the most optimum condition for buffering the volume changes during repeated cycling and provides facile pathways for Na-ion and electron transport in MoO3 .